Effect of Exogenous Melatonin on Corn Seed Germination and Seedling Salt Damage Mitigation Under NaCl Stress - Yuyu Zhang; Yuchuang Li; He Liu; Haili Xie; Jiani Liu; Jinzhu Hua; Mingchun Xiong; Huaifei Song; Chengjian Yong (Plants)
Maize is very sensitive to salt stress during seed germination and seedling growth periods, which can seriously affect the development of the maize industry. In this study, we applied exogenous melatonin (MT) to treat maize seeds and seedlings to investigate the alleviation mechanism of salt damage in maize. Phenotypic analyses showed that 100 µmol/L MT alleviated the effects of salt stress on maize seed germination, and germination index and vigor index were increased compared with salt treatment. MT also alleviated the effects of salt stress on biomass and photosynthesis of maize seedlings, and at a concentration of 100 µmol/L, root and shoot lengths were increased, Gs and Tr were significantly elevated, and LWUEint and LWUEins were decreased. MT also scavenged ROS accumulation, reduced MDA, H2O2, and O2− production, and increased antioxidant enzyme activities and osmoregulatory substances in maize seedlings, but too high a concentration exacerbated oxidative and osmotic stresses. In addition, MT reduced Na+ content and increased K+ content in leaves and roots of maize seedlings. The principal components analysis explained 99.1% of the total variance in the first two axes (PC1 and PC2), and the differences between the treatment groups along the PC1 and PC2 axes were obvious. Correlation analysis elucidated the correlation between the indicators. Random forest analysis showed that different treatments had significant effects on germination percentage (GP), free proline (FP), CAT, and leaf intrinsic water use efficiency (LWUEint). Partial least squares analysis showed that photosynthetic parameters and pigment content played an important role in the salt tolerance of maize seedlings. In conclusion, the application of exogenous MT can effectively alleviate the negative effects of salt stress on the growth of maize seeds and seedlings, especially at a concentration of 100 µmol/L, which is the most effective.